Steep increase in myopia among public school-going children in South India after COVID-19 home confinement - Krishnamurthy Saara; Saravanan Swetha; Rangavittal Subhiksha; Murali Amirthaa; Narayanan Anuradha (Indian Journal of Ophthalmology, 2022)
Purpose: Novel coronavirus has brought huge changes in lifestyle, especially among children. Reports indicate that the prevalence of refractive errors among children has increased due to home confinement. Hence, this study was done to understand the current status of refractive errors among children from public schools in southern India. Methods: This cross-sectional study was conducted as part of school eye screening conducted between September and October 2021. Children between 14 and 17 years of age from public schools underwent a three-phased comprehensive eye examination. Children identified with refractive errors and an equal proportion of children without any refractive errors underwent a survey on outdoor activities. Prevalence estimates and 95% confidence interval were calculated. Chi-square tests and regression analysis were used to understand the association between refractive error and other variables. Results: From the data of 3,850 (90.69%) children, the prevalence of vision impairment, refractive errors, and myopia in at least one eye was found to be 12.83% (n = 494), 21.51% (n = 828), and 19.53% (n = 752), respectively. The average myopic spherical equivalent error was found to be -2.17 ± 1.11D (range:-0.50 D to -14.00 D). Almost 96.82% of girls had less than 3 h of outdoor activities. Refractive errors were 7.42 and 2.77 times more (95% CI: 3.51-15.70), P < 0.001) among children who had outdoor activities less than 3 h per day and sleep less than 7 h per day. Conclusion: Comparing to previous studies from North Indian and South Indian public schools, this study reports a three- to six-fold rise in myopia post-home confinement among public school children from India.